Electromagnetic Torque Improvement of Doubly Salient Permanent Magnet Machine Using Pole Ratio Adjustment Technique - Sriwannarat, Warat; Seangwong, Pattasad; Siritaratiwat, Apirat; Fernando, Nuwantha; Dechgummarn, Yuttana; Khunkitti, Pirat (Frontiers in Energy Research, 2021)
This paper introduces the pole ratio adjustment technique to improve the torque characteristics of the doubly salient permanent magnetic machine (DSPM). The electrical characteristics of the machine, namely the magnetic field distribution, flux linkage, back-electromotive force (EMF), and cogging torque, were obtained under open-circuit conditions. The electromagnetic torque and ripple torque were examined under the loaded condition. The simulations, based on the 2D-finite element method, show that the optimal pole ratio for the DSPM structure is with 18 stator teeth and and 15 rotor poles. This optimal structure achieves a larger phase back-EMF than the conventional structure, as well as had a better magnetic flux path with a reasonable cogging torque. The on-load test also confirmes that the proposed optimal structure can produce a significantly higher electromagnetic torque than the conventional machine while maintaining a satisfactory torque ripple. Furthermore, an experimental prototype of the DSPM structure having 18/15 stator/rotor poles was fabricated and tested to verify the simulations. The experimental results were in good agreement with the simulations. The design technique and the fabricated prototype demonstrate the DSPM utilization for low-speed / high torque applications.